Maternal stress in pregnancy and adverse birth outcomes among women living with HIV during the COVID-19 pandemic - Paige L. Williams; Jessica Lee; Deborah Kacanek; Ellen G. Chadwick; Haleigh Civiletto; Claire A. Berman; Ann Aschengrau; Liz Salomon; Sue Siminski; Kathleen M. Powis (Frontiers in Reproductive Health, 2026)
Background Stress, depression, and racial discrimination occurring in pregnant women have demonstrated associations with adverse birth outcomes, but their role during and after the COVID-19 pandemic among women living with HIV (WLHIV) has not been evaluated. Methods We conducted surveys in pregnant and postpartum WLHIV participating in the US-based SMARTT study, asking them to report their experiences of social distancing, trauma and violence, and changes in housing, income, sleep and energy levels resulting from the COVID-19 pandemic. Women were also asked about their levels of perceived stress during pregnancy, experiences of discrimination, and depression and anxiety symptoms. Log-binomial regression models were used to evaluate associations of pandemic-related factors with perceived stress; linear and log-binomial models were used to evaluate associations of perceived stress with adverse birth outcomes. Results Among 125 WLHIV, 36.0% reported stress during pregnancy, 12.2% had moderate/severe depression symptoms, and 17.5% reported high discrimination levels. In adjusted models, social distancing behavior, impact of the pandemic on daily life, change in housing status, intimate partner violence, poor sleep quality, lower energy levels, and moderate/severe depression symptoms were associated with two- to five-fold higher risk of perceived stress in pregnancy. However, no association was observed between perceived stress and adverse birth outcomes. Conclusions Among WLHIV, over one-third experienced stress during pregnancy, associated with social distancing, trauma and violence, and other changes related to the COVID-19 pandemic. Optimal strategies are needed to screen pregnant and postpartum WLHIV for stress and mental health conditions and provide appropriate support during public health emergencies.